Measurement of Sub-femtomolar Concentrations of Prostate-Specific Antigen through Single-Molecule Counting with an Upconversion-Linked Immunosorbent Assay - Mickert, Matthias J; Farka, Zdeněk; Kostiv, Uliana; Hlaváček, Antonín; Horák, Daniel; Skládal, Petr; Gorris, Hans H (Analytical chemistry, 2019)
Single-molecule (digital) immunoassays provide the ability to detect much lower protein concentrations than conventional immunoassays. As photon-upconversion nanoparticles (UCNPs) can be detected without optical background interference, they are excellent labels for so-called single-molecule upconversion-linked immunosorbent assays (ULISAs). We have introduced a UCNP label design based on streptavidin-PEG-neridronate and a two-step detection scheme involving a biotinylated antibody that efficiently reduces nonspecific binding on microtiter plates. In a microtiter plate immunoassay, individual sandwich immune complexes of the cancer marker prostate-specific antigen (PSA) are detected and counted by wide-field epiluminescence microscopy (digital readout). The digital detection is 16× more sensitive than the respective analogue readout and thus expands the limit of detection to the sub-femtomolar concentration range (LOD: 23 fg mL-1, 800 aM). The single molecule ULISA shows excellent correlation with an electrochemiluminescence reference method. Although the analogue readout can routinely measure PSA concentrations in human serum samples, very low concentrations have to be monitored after radical prostatectomy. Combining the digital and analogue readout covers a dynamic range of more than 3 orders of magnitude in a single experiment.
Keywords: Immunosorbent Techniques; imunoanalýza; Photons; fotony; Nanoparticles; Streptavidin; Immunoassay; Dermoscopy; mužské pohlaví; Polyethylene Glycols; prostatický specifický antigen; zobrazení jednotlivé molekuly; polyethylenglykoly; Prostate-Specific Antigen; streptavidin; dermatoskopie; Humans; imunosorpční techniky; Diphosphonates; Single Molecule Imaging; nanočástice; bisfosfonáty; lidé; Male